Experimental study of flow and heat transfer in rotary air preheaters with honeycomb ceramics and metal corrugated plates. (5th February 2018) - Wang, Enlu; Li, Kai; Mao, Jinda; Husnain, Naveed; Li, Deli; Wu, Wei
Highlights: Two heat transfer elements including ceramic and metal plate were experimentally studied. The empirical correlations and ε - NTU relationship were deduced. Effects of some parameters on flow and heat transfer performance were analyzed. Higher flow and heat transfer performance occurred in metal heat transfer element. Bi-directional switching with single matrix was a novel experimental method for rotary air preheater. Abstract: The objective of this paper is to compare flow and heat transfer performance of rotary air preheaters consisting of honeycomb ceramics and metal corrugated plates. The experimental study was carried out by a bi-directional switching hot wind tunnel filled with single heat transfer matrix. The heat transfer and resistance empirical correlations, as well, the relationships between effectiveness and number of transfer unit were deduced from measured data. Under the same conditions, higher outlet air temperature and heat transfer effectiveness, lower pressure drop occurred in the metal heat transfer elements. The effects of switching time and flue gas velocity on flow and heat transfer performance of rotary air preheaters were analyzed. The experimental approach of bi-directional switching hot wind tunnel filled with single heat transfer matrix could be served as a performance analysis method for rotary air preheaters with different materials and passage shapes.